Effect of safety climate on safety behavior in employees: The mediation of safety motivation - Heryati, Ariska Nurul; Nurahaju, Rini; Nurcholis, Gartinia; Nurcahyo, Firmanto Adi (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2019)
The number of work accidents in production employees is high. One reason is the lack of compliance of employees with workplace safety rules. The necessary aspects that can improve workplace safety are safety climate and safety motivation. The purpose of this study was to examine the effect of safety climate on safety behavior both directly and indirectly mediated by safety motivation. Three scales were used in this study, namely the safety behavior scale, the safety climate scale, and the safety motivation scale. The Cronbach’s Alpha coefficients were 0.898, 0.922, and 0.896. The respondents were 78 employees in the production, processing, and quality assurance section. Data were analyzed using regression analysis. The result showed the direct effect (β = 0.272) and the indirect effect of safety climate on safety behavior (β = 0.281). The effect of climate safety on safety behavior was partially mediated by safety motivation.